Efficient elimination of RNA mycoviruses in aspergillus species using RdRp-inhibitors ribavirin and 2’-C-methylribonucleoside derivatives - Ikeda, Ayano; Chiba, Yuto; Kuroki, Misa; Urayama, Syun-ichi; Hagiwara, Daisuke (Frontiers in Microbiology, 2022)
RNA viruses in fungi (mycoviruses) are model systems for understanding the relationships between eukaryotic microorganisms and RNA viruses. To reveal the effects of mycoviruses on host fungi, it is essential to compare the phenotypes between isogenic fungal isolates with or without RNA virus infection. Since active entry machinery for RNA mycoviruses has never been identified, introducing mycoviruses to fungi is a difficult and time-consuming process. Therefore, most studies have tried to generate virus-free isolates from infected strains by eliminating the mycovirus. However, methods of elimination have not been evaluated in a quantitative and comparative manner. In this study, we established a method to remove mycoviruses from host cells using the antiviral drugs ribavirin, 2′-C-methylcytidine (2CMC), 2′-C-methyladenosine (2CMA), and 7d2CMA, and compared the efficiency of removal in virus-infected strains of Aspergillus fumigatus. The results indicated that treatment with the drugs removed RNA viruses of diverse proportions in the families Chrysoviridae, Mitoviridae, Partitiviridae, Polymycoviridae, and an unclassified RNA virus group. Viruses belonging to Narnaviridae were hardly eliminated by these antiviral treatments when they were the sole infectious agents. We found that 2CMC showed activity against a wider range of RNA mycoviruses compared to ribavirin, 2CMA, and 7d2CMA, although 7d2CMA also efficiently removed dsRNA viruses from the families Chrysoviridae, Partitiviridae, and Polymycoviridae. These results indicated that removal of mycoviruses depends on the specific viral species and antiviral drug. This is the first report demonstrating a preferential antiviral effect against mycoviruses, which will enhance research on microbial RNA viruses and support their elimination from economically important fungi such as edible mushrooms.